THE IMPLICATION OF PLUSES AND MINUSES OF RAHWANA’S BEHAVIOR TOWARDS INDONESIAN MODERN SOCIAL LIFE - I Nyoman Murtana (Universitas Sebelas Maret, 2019)
Rahwana – the King of Alengka in the wayang story of Nusantara is the king of the three worlds. The lower realm is inhabited by jinns, demons, the centre realm is inhabited by humans, and the upper realm is the nature of the Gods. Rahwana was a hermit and devoted worshiper to Shiva. He was given abundant gifts of supernatural powers and wealth. The Palace of the King of Alengka was very magnificent. The people were prosperous. Rahwana did everything he wanted to have. He could not be killed by anyone and with anything. If he was killed by the enemy, Rahwana would soon come back to life, because he had drunk an eternal drink from the God residing in his soul. That is why Rahwana was acting arbitrarily, without needing ethics. Rahwana could mate with other women he liked, even though they were married. The women of his choice were willing to date, for fear of threats. However, Rahwana's service was very satisfying. The husbands of the women he dated were silenced with property. The husband was afraid of his wife and king. That is one proof that God is the most merciful to the faithful devotees, without having to curb behavior with social rules, except the law of karma. The people of Alengka were free to express themselves, but they must be morally responsible. Law enforcers can be richer than entrepreneurs, because legal processes could be bought. The Unitary State of the Republic of Indonesia is inhabited by a diverse ethnic group with various languages and cultures. The Javanese, Sundanese, Lombok, and Balinese tribes are fond of watching the tradition of puppet show as a source of educational value and a reference to social behavior even though the Indonesian people live in a modern way characterized by industrial culture. This article aimed to find out the implications of the pluses and minuses of the behavior of Rahwana figure towards modern Indonesian society. Qualitative method is considered appropriate for data collection with the application of conflict theory. Through this theory, it is expected that there will be a motive for social conflict in modern Indonesian society.